Roof Box Shape Streamline Adaptation and the Impact towards Fuel Consumption - Abdul Latif M.F.; Hashim M.N.; Rashid M.Z.A; Azhari M.A.; Othman M.N. (MATEC Web of Conferences, 2017)
The fuel price hike is currently a sensational national issue in Malaysia. Since the rationalization of fuel subsidies many were affected especially the middle income family. Vehicle aerodynamic were directly related to the fuel consumption, were extra frontal area result a higher drag force hence higher fuel consumption. Roof box were among the largest contributor to the extra drag, thus the roof box shape rationalization were prominent to reduce the extra drag. The idea of adopting water drop shape to the roof box design shows prominent result. The roof box has been simulated using MIRA virtual wind tunnel modelling via commercial computational fluid dynamic (CFD) package. This streamline shape drastically reduce the drag force by 34% resulting to a 1.7% fuel saving compare to the conventional boxy roof box. This is an effort to reduce the carbon foot print for a sustainable green world.